Implementation of Nutritional Promotion Guidelines for Preschool Children with Overweight in a Childcare Centre - Nookong, Apawan -; Rungamornrat, Somsiri; Kraimongkol, Nattira; Puttisatean, Rungradee (Journal of Thailand Nursing and Midwifery Council, 2018)
Abstract: Objectives: To develop and implement nutritional promotion guidelines for preschool children with overweight in a childcare centre in central Thailand, and to compare their food consumption habits, physical activities, and percent of weight for height. Design: Action research. Methodology: The programme consisted of 2 phases: (1) the development of nutritional promotion guidelines based on input obtained from focus-group discussions with 10 people (childcare staff, teachers and cooks), 3 parents/guardians and 1 nurse; and (2) the implementation of the guidelines with the parents/guardians of 10 overweightaffected children, using Kolb’s experiential learning cycle approach. The qualitative data were analysed using content analysis. The children’s food consumption habits, physical activities and percent of weight for height before and after programme implementation were compared based on Wilcoxon Signed Rank Test. Results: After the development of the nutritional promotion guidelines for children with overweight in phase (1), the outcomes of programme implementation in phase (2) revealed a lack of nutritional knowledge and child-spoiling practices as the main causes of overweight in children. However, the children’s food consumption habits, physical activities and percent of weight for height before and after their participation in the programme were not signifcantly different (p > .05). Recommendations: All members of an overweight-affected child’s family are advised to take part in developing their own methods of nutritional promotion and create a mutual child-care agreement.